SHPRH and HLTF act in a damage-specific manner to coordinate different forms of postreplication repair and prevent mutagenesis - Lin, Jia-Ren; Zeman, Michelle K; Chen, Jia-Yun; Yee, Muh-Ching; Cimprich, Karlene A (Molecular cell, 2011)
Postreplication repair (PRR) pathways play important roles in restarting stalled replication forks and regulating mutagenesis. In yeast, Rad5-mediated damage avoidance and Rad18-mediated translesion synthesis (TLS) are two forms of PRR. Two Rad5-related proteins, SHPRH and HLTF, have been identified in mammalian cells, but their specific roles in PRR are unclear. Here, we show that HLTF and SHPRH suppress mutagenesis in a damage-specific manner, preventing mutations induced by UV and MMS, respectively. Following UV, HLTF enhances PCNA monoubiquitination and recruitment of TLS polymerase η, while also inhibiting SHPRH function. In contrast, MMS promotes the degradation of HLTF and the interactions of SHPRH with Rad18 and polymerase κ. Our data suggest not only that cells differentially utilize HLTF and SHPRH for different forms of DNA damage, but also, surprisingly, that HLTF and SHPRH may coordinate the two main branches of PRR to choose the proper bypass mechanism for minimizing mutagenesis.